Can Hybrid Group Guidance with the Values-based Cognitive Reconstruction Technique "Ngudi Kasampurnan" Increase Religious Tolerance in Students? - Zamroni, Edris; Gudnanto, Gudnanto; Lestari, Indah; Sulistyowati, Hesti; Utomo, Setyo Budi (Bulletin of Counseling and Psychotherapy, 2024)
Religious tolerance is a crucial issue that often becomes a problem in student interactions in schools, especially schools that are diverse culturally, religiously, and in the identity of religious organizations. This study aims to test the effectiveness of hybrid group guidance services using the value-based cognitive reconstruction technique "ngudi kasampurnan" for high school students. This research involved 30 class XI high school students in Kudus Regency who were divided into two groups, namely the control group and the experimental group. The intervention was implemented in 9 (nine) stages, either face-to-face synchronous, virtual face-to-face, or synchronous, by applying the values-based cognitive reconstruction technique "ngudi kasampurnan" as a modification and novelty of this research. The effectiveness test was carried out using the Mann-Whitney Test method with the help of SPSS 23. The results showed that the control group that was given the intervention experienced significant changes, as indicated by a Z value of -4.705 and a P value of 0.000, which means there was a considerable change. Meanwhile, the control group had a Z value of -1.623 and a P value of 0.104, which means there was no significant effect. These results show that hybrid intervention with the value-based cognitive reconstruction technique "ngudi kasampurnan" is more effective in increasing students' religious tolerance. Furthermore, it is hoped that there will be efforts to modify and collaborate technological sophistication with local wisdom values, which will still serve as guidelines for Indonesian society.